Psychological and pedagogical manipulation in educational (Actual Problems of Psychology in Educational Institutions, 2021)
In the article the content of the concept of psychological andpedagogical manipulation according to the views of various scientists isconsidered and analyzed. Also, the concept of psychological influence iscovered. It was found out what kind of interaction there is between thestudent and the teacher. Different types of manipulations are identified andbriefly characterized. The relevance or its absence in the use of differenttypes of manipulation in the pedagogical process is analyzed. The processof psychological and pedagogical manipulation in educational institutions isstudied. The level of awareness of the subjects in the issue of manipulativeprocess is determined.
Keywords: psychological influence, manipulative techniques, pedagogical influence